PENGUATAN LITERASI MEDIA DIGITAL MAHASISWA PAI IAI ALMUSLIM DALAM MENINGKATKAN PRESTASI BELAJAR - Jufrizal, Jufrizal (Ta’dib: Jurnal Pemikiran Pendidikan, 2022)
This study aims to provide digital media literacy reinforcement for IAI Almuslim students, especially in the PAI Study Program to improve learning achievement. In an all-digital era like now, of course there are positive and negative impacts from the progress of this era. If not consumed properly, the wrong information can be conveyed through these digital media. One of the biggest consumers of digital media is students. Students must understand media literacy so that they are not negatively affected by the media, and can get positive information from the media from various sources. This study uses a qualitative method with a descriptive analysis approach. Data collection techniques by means of observation, interviews and documentation on the IAI Almuslim Aceh campus.